Experimental Analysis using an Innovative Catalytic Converter coated with Nano-particles for Pollution Control from Automobiles. Issue 1 (November 2021) - Thakur, Mukesh; Senanayake, Rohan
Abstract: Air pollution control has become the area of interest due to the ever increasing air pollution problem from the automobiles. Several researchers have conducted several experiments to control the air pollution concentration from automobiles by using several techniques but this area has a wide scope for improvement. This research paper is based on an experiment conducted on a Four Stroke Spark Ignition engine test rig using an Innovative catalytic converter which was coated with nano-particles to estimate its effectiveness in air pollution control. The results of the experiment conducted clearly indicate that the Innovative design of catalytic converter is effective in air pollution control from automobiles.